Availability Rice Procurement Policy Scenarios to Maintain Price Stability - Joko Suprianto (Fakultas Teknik Universitas Bhayangkara, 2016)
East Java province with a population of more than 37 million people, mostly consume rice as a staple food. SUSENAS data in 2010 showed that the people of East Java rice consumption stood at 125kg / capita / year. With a population growth rate of 0.76% per year, the population of East Java increased as much as 3,659 lives each year. Addition of the population of these consequences on additional ballooning rice requirement of 457 409 tonnes / year. In this study, using the approach of dynamic system models with three scenarios, the Land Intensification scenario 1, scenario 2 Ekstensifiaksi land, and scenario 3 Combined Intensification and extensification Land. The most optimal results from the third scenario is the scenario 3 (combined intensification and extensification Land), whereas in the scenario 3 rice production at the beginning of the simulation in 2012 reached 6.5359 million tons and production at the end of the simulation in 2021 reached 7.61593 million tonnes ( the most optimal). While the price of rice at the beginning of the simulation in 2012 reached Rp 7,153 and the price of rice at the end of the simulation in 2021 reached Rp 13.213.Pada scenario 3 rice prices are relatively stable from year 2012 to 2021 between Rp 7,153 to Rp 13 213.Rice,